(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the roles, challenges, and contributions of women judges in Uzbekistan. It delves into their professional activities, the impact they have on the judiciary, and the societal and institutional barriers they face. Through a comprehensive analysis of literature, a mixed-methods approach involving qualitative interviews, and quantitative data analysis, the study highlights the progress and remaining challenges for women in the judiciary.